Retrospective on Exploring MXene-Based Nanomaterials: Photocatalytic Applications - Syed Irfan; Sadaf Bashir Khan; Muhammad Aizaz Ud Din; Fan Dong; Deliang Chen (Molecules, 2023)
Nanostructural two-dimensional compounds are grabbing the attention of researchers all around the world. This research is progressing quickly due to its wide range of applications in numerous industries and enormous promise for future technological breakthroughs. Growing environmental consciousness has made it vital to treat wastewater and avoid releasing hazardous substances into the environment. Rising consumer expectations have led to the emergence of new, frequently nonbiodegradable compounds. Due to their specific chemical and physical properties, MXenes have recently been identified as promising candidates. MXenes are regarded as a prospective route for environmental remediation technologies, such as photocatalysis, adsorption, and membrane separation, and as electrocatalytic sensors for pollution recognition because of their high hydrophilicity, inherent chemical nature, and robust electrochemistry. The development of catalysts based on MXene materials for the photocatalytic breakdown of pharmaceutical wastes in polluted water is critically evaluated in this study. With an emphasis on the degradation mechanism, the photocatalytic degradation of antibiotics using MXenes and MXene-based nanocomposites is explained in depth. We emphasize the significant difficulties in producing MXenes and their composites, as well as in the degradation of drugs. The successful use of MXenes in water filtration and suggestions for future study are also presented.